Clinico-epidemiological study of Lichen Planus and its association with Hepatitis C - Shrestha, Rima; Shrestha, Samir (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: The relationship between lichen planus and hepatitis C virus (HCV) remains controversial. The aim of this study is to find out the incidence of lichen planus in different age and sex groups, occupation, seasonal variation and familial association. And to correlate any association between lichen planus and hepatitis C virus. Methods: This case control study was conducted at National Academy of Medical Sciences, Bir hospital and Shree Birendra army hospital from July 2006 to Oct 2007. The study included 100 patients with typical feature of lichen planus of skin and mucous membrane. Results: Out of hundred patients with lichen planus 51% were male and 49% were female, Koebner phenomenon was found in 69%. LP was more commonly found in the extremeties 81.9% in leg, 86.7% in forearms, 51.8% in thigh; followed by dorsa of hands 36.7%, arm 25%, and dorsa of feet 18.1%, Face & scalp were less involved with 15% & 4% only. Most of the LP were encountered during months may to august. Oral lichen planus (OLP) was seen in 7 cases. None of the patient with LP had concomittant HCV infection association. Conclusion:Lichen planus is one of the common skin disorder encountered in the dermatological practice without association with hepatitis C virus infection in this part of the world.